TELAAH KRITIS PENGELOLAAN DANA DESA DENGAN PENDEKATAN MAQASHID SYARIAH DI DESA TANJUNG SALAH KABUPATEN KUBU RAYA KALIMANTAN BARAT - Rasiam Rasiam (Fakultas Syariah (Syari'ah Faculty ), 2021)
Critical Analysis of Village Fund Management Using Maqashid Syariah Approach in Tanjung Saleh Village, Kubu Raya Regency.The birth of Law number 6 of 2014 concerning Villages is a form of the presence of the Indonesian government to its people. The presence of the government to fulfill the needs and basic needs of its people is getting clearer, it can be seen in article 1 paragraph 2 that village funds are funds sourced from the State Revenue and Expenditure Budget for villages that are transferred through the Regency / City Regional Budget and Expenditure and used to finance governance, development implementation, community development, and community empowerment. On the one hand, the village fund program must make observations and evaluations related to the values of the program being carried out. This study analyzes the village fund program using the Maqashid Syariah approach with five basic principles, namely maintaining religion, soul, mind, descent and property. For that research questions focused on; management of village funds in Tanjung Saleh, Kubu Raya Regency with the Maqashid Syariah approach to safeguarding religion (al-Din), soul (al-Nafs), mind (al-'Aql), descent (al-Nasl), property (al-Maal) For that research questions focused on; management of village funds in Tanjung Saleh, Kubu Raya Regency with the Maqashid Syariah approach to safeguarding religion (al-Din), soul (al-Nafs), reason (al-'Aql), descent (al-Nasl), property (al-Maal) with the aim of exploring and understanding the concept of village funds in terms of 5 (five) principles of Maqashid Syariah which are inspired by sharia values. This research was a field research with qualitative descriptive methods and normative juridical. The conclusion of this research is that there has been a harmonization between the values in the Maqashid Syariah in terms of maintaining religion, soul, mind, descent and property in village fund programs in Tanjung Saleh from 2017 to 2019. The work programs of the village of Tanjung Saleh, Sungai Kakap District, Kubu Raya Regency, West Kalimantan, from 2017 to 2019 which are related to maintaining religion was 9%, programs related to keeping the soul was 266%, programs related to maintaining intelligence was 16%, programs related to maintaining descent was 4%, and programs related to safeguarding property was 6%. From this percentage, it shows the harmonization of maqashid with village programs that have been implemented for welfare and services to the community. The interesting thing from the conclusion above is the finding of life-preserving programs that is very dominant compared to other programs so that it can be measured that keeping the soul is very important. Keeping the soul is also a public program that the benefits can be felt by people across ethnicities and religions. It means that inclusive programs without any discrimination.